Immobilization strategies biomedical, bioengineering and environmental applications - Tripathi, Anuj; Melo, Jose Savio (Gels horizons: from science to smart materials, 2021)
This book delves into the field of immobilizing biologically active and non-active molecules. It discusses the designing strategy of immobilization and the current state-of-the-art applications for advancing biomedical, agricultural, environmental and industrial practices. It focuses on aspects ranging from fundamental principles to current technological advances at multi-scale levels (macro, micro, and nano) which are suitable for cell, enzyme, and nano-catalyst based applications. Written by experts from across the globe, the contents deal with illustrated examples of molecular and cellular interactions with materials/scaffolds and discussions on factors that can affect the functionality and yield of the process. With its discussions on material science, design of delivery vehicles, separation science, additive manufacturing, agriculture and environmental science, this book will be a useful reference for researchers across multiple disciplines